Penerapan Metode Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Keaktifan dan Hasil Belajar Pendidikan Agama Islam - Dede, Dede (Yayasan Darusssalam Bengkulu, 2020)
Initial observations found that the activities of teachers and students were passive and learning outcomes were low. This is assumed because the learning method used is still using conventional methods, which tend to be teacher centered. The purpose of this study was to determine the activities of teachers and students and the application of the Make A Match cooperative method to have a positive impact on QS learning outcomes. Al-Falaq. The study used a classroom action research method in class IV SD Negeri 219 Bengkulu Utara. Data obtained through observation and test learning outcomes. The steps used are planning, implementing, observing and reflecting. These results indicate that student learning outcomes increase. The average learning outcomes of students from cycle I was 68 and increased in cycle II to 78.2 (an increase of 10.2). Individual learning completeness in the first cycle reached 36.8% and in the second cycle it reached 78.9% (an increase of 42.1%). In the aspect of knowledge, students mastered more QS words and verses. Al-Falaq and its meaning. The psychomotor aspect has succeeded in establishing communication between students, because it happens that the cards they hold are in pairs